Hydrochemical Profile of Banjosa Lake Poonch, Kashmir - ASLAM MIRZA, M.; KHUHAWAR, M.Y.; ARAIN, RAFEE (Asian Journal of Chemistry, 2010)
The hydrochemical profile study of Banjosa Lake was conducted through systemic sampling, spacially and temporally, during 2004-2005. The pH averaged 7.25, EC 231 μS/cm and TDS 148 mg/L. Chlorides, sulphates, nitrate nitrogen, total nitrogen, orthophosphates and total phosphates, showed corresponding mean values as 24.63, 15.32, 2.81, 1.30, 0.16 and 0.20 mg/L. November and February (2004 and 2005) samples for BOD and COD indicated COD exceeding threshold values set by WHO. Atomic absorption spectrometry determination of major (Na+, K+, Ca2+, Mg2+) and trace level metals (Fe2+, Cu2+, Ni2+, Zn2+, Cd2+, Pb2+, Co2+) was also carried out. Estimation of sodium absorption ratio, percentage sodium and residual sodium carbonate values recommend it for agricultural uses.